Gambaran Motivasi Pemberian Air Susu Ibu pada Ibu Postpartum di Wilayah Kerja Puskesmas Rawasari - Indah Najwa Syalsabilah; Sri Mulyani; Meinarisa Meinarisa; Muthia Mutmainnah; Fadliyana Ekawaty (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to describe the motivation for breastfeeding among postpartum mothers in the working area of the Rawasari Public Health Center. Methods: The research employed a quantitative approach with a cross-sectional design. The population consisted of all postpartum mothers in the area, and a total of 71 respondents were selected using purposive sampling. The research variable was breastfeeding motivation, measured using the Breastfeeding Motivational Instructional Measurement Scale or BMIMS. Data were analyzed descriptively to illustrate respondents’ motivation levels. Results: Most respondents had a moderate level of motivation, totaling 48 respondents or 67.6 percent, while 23 respondents or 32.4 percent showed a high level of motivation. Conclusion: The majority of postpartum mothers demonstrated fairly good motivation in breastfeeding; however, enhanced education and family support are still needed to optimize breastfeeding practices.